(Lipase Catalysed Intersterification of Red Palm Oil and Coconut Oil Blends to Produce B-Carotene Riched Raw Spreads) - Fitri Hasrini, Reno; -, Sugiyono; Hariyadi, Purwiyatno; Andarwulan, Nuri (Warta Industri Hasil Pertanian, 2009)
Red palm oil has several characteristics which is very raw spread, especially their high carotenoid content which have many advantages for human health. Enzymatic interesterification (IE) with saturated and middle-along chain fatty acid (coconut oil) is one effective ways improve their physical propertise. the objective of this research was to obtain the best formulation of red palm oil coconut oil blends which have the most similar characteristics with raw spreads commercial and have high B-carotene content. The in this research were (1) Chemical properties analysis from Crude Palm Oil (CPO), including water content, free fatty acid, peroxide value, iod value, and carotenoid total, (2) Refining and chemical properties analysis of Neutralized Red Palm Oil (NRPO), including water content, free fatty acid, peroxide value, iod value, and carotenoid total, (3) Fractionation of neutralized Red Palm Oil (NRPO), (4) Enzymatic interesterification and physicochemical properties analysis, including slip melting point (SMP), carotenoid total, solid fat content (SFC), and fat crystallization behavior. The results showed that product of enzymatic interesterification such as SMP and SFC profiles were higher than without enzymatic interesterification treatment, carotenoid total was not change significantly, and the crystal sizes were larger than treatment before. Enzymatic interesterification results very significant changing on physical properties from NRPO and Rpo and still have high total carotenoid. Formulation of (Rps/Rpo)/CNO with ratio 75:25, 77,5:12,5 and 82,5:17,5 b/b had most similar physical properties with profile raw spreads retail and industry. SMP value of there ratio already included in SMP commercial spreads range that are 32,63; 33,60 and 34,86 oC. After enzymatic interesterification process, total carotenoid only decreased 1,85; 2,97 and 2,93% (363,16; 378,21 and 392,81 ppm become 356,43; 366,72 and 381,32 pmm), and SFC profile on 20, 30 40 oC were similar with SFC profile raw spreads and industry.